Confirmatory Factor Analysis on Store Atmosphere Variables of Coffee Shops in Kuningan City, West Java - Roy Septyanto; Muhamad Anas; Taofik Muhammad Hidayat; Wachdijono Wachdijono (Riviera Publishing, 2025)
This study investigates the impact of store atmosphere on consumer behavior in coffee shops in Kuningan City, West Java. The research employs Confirmatory Factor Analysis (CFA) to validate and measure the dimensions that contribute to the store atmosphere, which include lighting, music, cleanliness, aroma, interior design, and exterior design. A survey was conducted among 120 coffee shop consumers to gather data on their perceptions and experiences. The findings reveal that the interior design dimension has the most significant influence on customer satisfaction, followed closely by cleanliness and exterior design. The results indicate that a well-structured and aesthetically pleasing atmosphere enhances consumer loyalty and encourages repeat visits. This research not only fills a methodological gap in existing literature but also provides practical implications for coffee shop owners aiming to improve their marketing strategies. By focusing on the identified dimensions, coffee shops can create a more inviting and comfortable environment, ultimately leading to increased customer engagement and satisfaction. This study contributes to the broader understanding of consumer behavior and the importance of sensory elements in retail settings.